Amaranthaceae endémicas del Perú - León, Blanca (2006)
The Amaranthaceae are represented in Peru by 13 genera and 72 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), basically herbs and shrubs. Here we recognize as endemics eight species and two varieties in six genera. These 1o endemics taxa grow mostly in Desert Shrubland and Mesoandean regions, between 500 and 2400 m elevation. No endemic Amaranthaceae have been registered to date within Peru’s protected areas system.